"I know it, but… I have the word on the tip of my tongue!" TOT as phenomenon to re-thinking Metacognition and Feeling-of-knowing in Psychology ("Lo sé, pero… ¡tengo la palabra en la punta de la lengua!": PDL como fenómeno para repensar la metacognición y la sensación de saber en Psicología). Issue 2 (3rd April 2022) - Fossa, Pablo; Gonzalez, Nicolás; García-Huidobro, Camila; Barros, Matías; Sanhueza, María-Isabel
ABSTRACT: The phenomenon of having a word on the tip-of-the-tongue (TOT) is an inherent psychological experience that emerges from an unsuccessful cognitive effort aimed at finding the right word to express a specific thought. From a Vygotskian perspective, this can be understood as a dynamic relationship between psychological processes that evolves over time, especially between thought and language, with these functions at times intersecting and later bifurcating — even aligning in parallel — during microgenetic human development. Following Vygotsky's postulates, in this article we explore the TOT experience as an episodic gap between thought and language during daily psychological activity. Then, the notion of metacognition in psychology is adjunctly revisited and reviewed. Based on theoretical developments on the notion of feeling-of-knowing, the TOT experience and metacognition are reframed as affective phenomena and the accuracy of the traditional interpretation of metacognition as a cognitive-intellectual monitoring system is put into question. Finally, the article discusses possible contributions the TOT phenomenon and the feeling-of-knowing might offer to educational practices and processes.